Soybean Consumption and Postpartum Blood Pressure Reduction: A Potential Solution? A Literature Review - Mardiyana, Shinta Lia Nana; Sri Rahayu; Sri Endang Windiarti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Hypertension is called a silent killer, hypertension in postpartum mothers can be caused by high blood pressure that persists since pregnancy or due to actions during childbirth. Hypertension that occurs during the postpartum period can become chronic high blood pressure and in the long term can have an impact on kidney tissue damage, coronary heart disease, stroke, and death. Non-pharmacological efforts are needed to prevent complications due to hypertension, one of which is the use of plants that contain high potassium, magnesium, and fiber which function as Antihypertensives. The purpose of the study was to determine the potential of soybeans as an alternative antihypertensive solution. The research method used Preffered Reporting Items for Systematic Review and Meta-analysis (PRISMA). The literature search used Science Direct, PubMed, Research Gate, and Google Scholar. The literature review used is articles published in the last 6 years (2021-2025), the keywords used in the search include “soybean” and “antihypertension”. 6 articles were obtained to be analyzed according to the specified criteria. The results showed that regular consumption of soybeans and processed soy foods can have an impact on reducing systolic and diastolic blood pressure. Not only that, soy consumption also has benefits as a nutraceutical to reduce bad cholesterol and increase good cholesterol to play a role in maintaining heart health and has the potential to reduce blood pressure.